2013
DOI: 10.1055/s-0033-1337119
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Pain Management after Spinal Fusion Surgery: An Analysis of the Efficacy of Continuous Infusion of Local Anesthetics

Abstract: Spinal fusion surgery is a major surgery that results in severe postoperative pain, therefore pain reduction is a primary concern. New strategies for pain management are currently under investigation and include multimodal treatment. A 3-year retrospective analysis of patients with idiopathic scoliosis undergoing spinal fusion surgery was performed at our hospital, assessing patient pain scores, opioid use, and recovery. We evaluated the effect of adding continuous infusion of local anesthetics (CILA) to a pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 36 publications
1
31
0
1
Order By: Relevance
“…As a result, approximately 0.5 mg/kg less opioid was required within the first 24 hours. 20 In the present study the authors performed wound infiltration with 50% diluted levobupivacaine solution before wound closure. The recommended local anesthetic in wound infiltration is ropivacaine due to its intrinsic vasocontrictive effect and its lesser potential for cardiotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, approximately 0.5 mg/kg less opioid was required within the first 24 hours. 20 In the present study the authors performed wound infiltration with 50% diluted levobupivacaine solution before wound closure. The recommended local anesthetic in wound infiltration is ropivacaine due to its intrinsic vasocontrictive effect and its lesser potential for cardiotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…(19) It has been emphasized in the literature that administration of narcotic analgesics through patient controlled analgesia (PCA) after spinal surgery is very beneficial in pain management. (19,20) PCA, frequently used in vertebrae surgery, has been reported to have advantages like performing activities more comfortably, provision of more effective analgesia at lower doses, having fewer side-effects and reducing stress. (20) Nonsteroidal anti-inflammatory drugs and corticosteroids are used in combination with narcotics for pain management.…”
Section: Discussionmentioning
confidence: 99%
“…(20) Nonsteroidal anti-inflammatory drugs and corticosteroids are used in combination with narcotics for pain management. (19,21) Several studies have shown that multimodal analgesia is more effective in reduction of pain in children. (22,23) Besides, transcutaneous electrical nerve stimulation (TENS) has been reported to decrease analgesia needs and have few side-effects.…”
Section: Discussionmentioning
confidence: 99%
“…9,34 Two retrospective level III studies support the use of continuous infusion of local anesthesia in the postoperative care of the spine patient. 35,36 In a review of patients who underwent posterior cervical fusion, Elder et al 35 compared 25 patients who received the standard pain regimen and a continuous infusion of bupivacaine (0.5%) via elastomeric pump with 25 matched control patients who were treated with the standard regimen. Patients who received the continuous bupivacaine infusion had improved pain control and reduced opioid consumption in the first 4 days postoperatively.…”
Section: Local Anesthesiamentioning
confidence: 99%